Decision Support System for Major Selection in Higher Education Using the Simple Additive Weighting Method - Novita, Dela; Lidya Wati, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Choosing a college major is an important decision that affects a student's future, where the wrong choice can lead to incompatibility, academic difficulties, and wasted expenses. To help students determine a major that suits their interests, talents, and other criteria such as cost, accreditation, and job prospects, this study developed a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method. The research was conducted using the Rapid Application Development (RAD) method, encompassing planning, design, coding, and testing stages, as well as data collection through interviews and document analysis. The results indicate that the SAW method is effective in providing major recommendations through ranking based on the weights of relevant criteria, thereby helping students make objective and swift decisions. As a result, this system simplifies the major selection process, enhances efficiency, and reduces the risk of errors in decision-making.